2-methyl-1H-indole-3-carbaldehyde 4-hydroxybenzoylhydrazone - Ali, Hapipah Mohd; Ng, S.W.; Xie, M.J.; Najwa, M.I. (International Union of Crystallography, 2006)
The NH group of the methylindolecarbaldehyde moiety and the OH group of the hydroxybenzoylhydrazone moiety of the title compound, C17H15N3O2, interact to form a linear chain; adjacent chains are linked through the amide -N(H)-C(=O)- portion of the molecule to form a tightly held three-dimensional network structure.